Spectroscopic properties and upconversion mechanisms in Er3+-doped fluoroindate glasses - Catunda, T.; Nunes, L. A. O.; Florez, A.; Messaddeq, Younes [UNESP]; Aegerter, M. A. (American Physical Society (APS), 1996)
Fluorindate glasses containing 1,2,3,4 ErF3 mol % were prepared in a dry box under argon atmosphere. Absorption, Stokes luminescence (under visible and infrared excitation), the dependence of 4S3/2, 4I11/2, and 4I13/2 lifetimes with Er concentration, and upconversion under Ti-saphire laser excitation at λ=790 nm were measured, mostly at T=77 and 300 K. The upconversion results in a strong green emission and weaker blue and red emissions whose intensity obeys a power-law behavior I∼Pn, where P is the infrared excitation power and n=1.6, 2.1, and 2.9 for the red, green, and blue emissions, respectively. The red emission exponent n=1.5 can be explained by a cross relaxation process. The green and blue emissions are due to excited state absorption (ESA) and energy transfer (ET) processes that predict a factor n=2 and n=3 for the green and blue emissions, respectively. From transient measurements we concluded that for lightly doped samples the green upconverted emission is originated due to both processes ESA and ET. However, for heavily doped samples ET is the dominant process.